Iran-Russia-China Trilateral Naval Exercise : China’s New Mideast Strategy? - Yang, Zi (2020)
In the first-ever such manoeuvre, the navies of Iran, Russia, and China concluded 2019 with a joint exercise not far from the Strait of Hormuz. Does the joint exercise foreshadow a shift in China’s Middle East strategy that would benefit Iran?